Cognitive Function before and during Treatment with Selective Serotonin Reuptake Inhibitors in Patients with Depression or Obsessive-Compulsive Disorder. (15th August 2016) - Sayyah, Mehdi; Eslami, Kaveh; AlaiShehni, Shabnam; Kouti, Leila
Abstract : Objectives . Identification of adverse effects of selective serotonin reuptake inhibitors (SSRIs) is of great importance due to their extensive use in medicine. Some studies have reported the effects of SSRIs on cognitive functions, but the results are conflicting. This study was designed to assess the effect of these drugs on cognition of patients with depression or obsessive-compulsive disorder (OCD). Methods . Patients with depression or OCD, naïve to therapy, and candidates of receiving one drug from SSRI class, voluntarily, entered this study. Mini-Mental State Examination (MMSE) test was the tool to assess their cognitive functions. MMSE scores of each patient were recorded prior to taking SSRIs and at weeks 3, 5, and 8 of drug therapy. Results . 50 patients met our inclusion criteria, with a baseline mean MMSE score of 23.94. At 3, 5, and 8 weeks of treatment, the mean scores were 22.1, 21.4, and 20.66, respectively. With ap value of <0.0001, the gradual decline was statistically significant. Conclusion . The MMSE scores of our patients showed a gradual decline over the consecutive weeks after taking SSRI drugs. It seems that the use of SSRIs in patients with depression or OCD, can cause cognitive dysfunction in the acute phase of treatment.